Role of the nifB1 and nifB2 Promoters in Cell-Type-Specific Expression of Two Mo Nitrogenases in the Cyanobacterium Anabaena variabilis ATCC 29413 - Vernon, Susan A. (J Bacteriol, 2017)
Anabaena variabilis ATCC 29413 has one Mo nitrogenase that is made under oxic growth conditions in specialized cells called heterocysts and a second Mo nitrogenase that is made only under anoxic conditions in vegetative cells. The two large nif gene clusters responsible for these two nitrogenases are under the control of the promoter of the first gene in the operon, nifB1 or nifB2. Despite differences in the expression patterns of nifB1 and nifB2, related to oxygen and cell type, the regions upstream of their transcription start sites (tss) show striking homology, including three highly conserved sequences (CS). CS1, CS2, and the region just upstream from the tss were required for optimal expression from the nifB1 promoter, but CS3 and the 5′ untranslated region (UTR) were not. Hybrid fusions of the nifB1 and nifB2 upstream regions revealed that the region including CS1, CS2, and CS3 of nifB2 could substitute for the similar region of nifB1; however, the converse was not true. Expression from the nifB2 promoter region required the CS1, CS2, and CS3 regions of nifB2 and also required the nifB2 5′ UTR. A hybrid promoter that was mostly nifB2 but that had the region from about position −40 to the tss of nifB1 was expressed in heterocysts and in anoxic vegetative cells. Thus, addition of the nifB1 promoter region (from about position −40 to the tss of nifB1) in the nifB hybrid promoter supported expression in heterocysts but did not prevent the mostly nifB2 promoter from also functioning in anoxic vegetative cells. IMPORTANCE In the filamentous cyanobacterium Anabaena variabilis, two Mo nitrogenase gene clusters, nif1 and nif2, function under different environmental conditions in different cell types. Little is known about the regulation of transcription from the promoter upstream of the first gene of the cluster, which drives transcription of each of these two large operons. The similarity in the sequences upstream of the primary promoters for the two nif gene clusters belies the differences in their expression patterns. Analysis of these nif promoters in strains with mutations in the conserved sequences and in strains with hybrid promoters, comprising parts from nif1 and nif2, provides strong evidence that each promoter has key elements required for cell-type-specific expression of the nif1 and nif2 gene clusters.